ANALISIS SWOT TERHADAP DINAMIKA SOSIAL DAN EKONOMI MASYARAKAT PERBATASAN: STUDI KASUS PULAU SEBATIK INDONESIA-MALAYSIA - Moh. Falmes Lakadjo; Widiyanti Tanaiyo; Siti Febriyanti Mohamad; Mohamad Ikbal Kadir (LPPM Universitas Muhammadiyah Gorontalo, 2026)
Border areas possess distinctive characteristics shaped by cross-border social, economic, and institutional interactions. Sebatik Island, located on the Indonesia–Malaysia border, faces various opportunities and challenges that influence community dynamics and regional development. This study aims to analyze the social and economic dynamics of the Sebatik Island community using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) approach to identify strategic factors affecting border area development. A qualitative descriptive approach was employed. Data were collected through in-depth interviews, field observations, documentation, and literature review, and analyzed using the interactive model of Miles, Huberman, and Saldaña, followed by SWOT analysis to formulate strategic development alternatives. The findings indicate that community dynamics are strongly influenced by cross-border interactions that shape social relations, trade activities, and economic mobility. Social capital, a strategic geographical position, and local economic potential constitute the main strengths of the area, while dependence on Malaysian goods, limited infrastructure, and suboptimal public services remain significant weaknesses. Opportunities arise from government policies on border development and expanding cross-border economic cooperation, whereas illegal trade, development disparities, and economic dependence on neighboring countries pose substantial challenges. The study concludes that sustainable border area development requires integrated strategies encompassing local economic empowerment, infrastructure improvement, better public services, and strengthened border governance to enhance community welfare while reinforcing national sovereignty